Analysis of the pharmacological activities of Handroanthus serratifolius (Vahl) S.Grose (Research, Society and Development, 2022)
Handroanthus serratifolius (Vahl) S.Grose, (syn. Handroanthus albus; syn. Tabebuia serratifolia), popularly known as yellow-ipê, belongs to the Bignoniaceae family. Plants of this family have several pharmacological activities described in the literature, which occur due to the presence of secondary metabolites, such as lapachol, which induces oxidative stress in cells and can be effective against obligate intracellular parasites and cancer cells. The aim of the article was to analyze the pharmacological properties present in chemical compounds isolated from different parts of H. serratifolius (Vahl) S.Grose, (syn. H. albus; syn. T. serratifolia). The study is an integrative literature review, carried out in the databases Science Direct, Google Scholar, Embase, MEDLINE via PubMed, Web of Science and the Virtual Health Library (VHL), based on works published in the last six years, in Portuguese and English, that have fully addressed the topic under investigation. It was observed in the analyzed studies that the species of yellow ipe have antibacterial, antinociceptive, antifungal, antiinflammatory, antiparasitic, cytotoxic, antileishmanial and antiplasmoid activities, and that these activities can be found in leaf and stem extracts. Furthermore, lapachol has been shown to be responsible for some of these pharmacological properties. Therefore, it can be concluded that Handroanthus serratifolius is a potential source for research and development of new substances with different pharmacological applicability.